1991
DOI: 10.2172/10150157
|View full text |Cite
|
Sign up to set email alerts
|

Water resources data, Kentucky. Water year 1991

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The accuracy of discharge estimates depends on the stability of the stage-discharge relation and the frequency of discharge measurements (McClain et al, 1997). Most of the discharge estimates used in this study are reported as 'good' in the State water-data reports.…”
Section: Discharge and Nutrient Analysismentioning
confidence: 87%
“…The accuracy of discharge estimates depends on the stability of the stage-discharge relation and the frequency of discharge measurements (McClain et al, 1997). Most of the discharge estimates used in this study are reported as 'good' in the State water-data reports.…”
Section: Discharge and Nutrient Analysismentioning
confidence: 87%
“…1). The average discharge near its mouth is 7,787 m 3 á s A1 (1928± 1995McClain et al 1995) with peak¯ows generally in March (Fig. 2).…”
Section: Study Sitesmentioning
confidence: 96%
“…Field experiments were conducted at two sites in the upper Mississippi River, just below Winona, MN (Mississippi River kilometres 1157 and 1164), and at three sites on the Ohio River just upstream of Louisville, KY (Ohio River kilometres 922, 927 and 932). The average annual discharge at Winona is 807 m 3 s -1 (historical daily range ϭ 64-7476 m 3 s -1 for 66 years of data; Mitton, Hess & Guttormson, 1995), whereas the discharge at Louisville is 3273 m 3 s -1 (daily range of 59-31 432 m 3 s -1 for 63 years of data; McClain, Byrd & Brown, 1994). The Mississippi and Ohio Rivers have relatively natural hydrographs in comparison to rivers with high dams (J. H. Thorp, unpublished data) and flow even during the summer, when the navigation dams partially impede them.…”
Section: Site Descriptionmentioning
confidence: 99%